2014
DOI: 10.15835/nbha.42.2.9671
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Propagation of Sweet and Sour Cherry Rootstocks

Abstract: The paper presents a protocol for micropropagation of Prunus sp. rootstocks included in the sweet and sour cherry breeding program. Germplasm diversity for rootstock breeding derives from natural populations, where conditions and biological vectors for systematic infection with viral diseases are constantly present. The establishment of aseptic culture depends primarily on the explant type, as all selections were collected from natural habitat. For nearly all investigated selections, dormant buds were the favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…The number of roots per explant and root length were highest in the medium supplemented with 2 mg•l -1 IBA (Table 8). Similar results were reported by Dorić et al (2014) who obtained the maximum number of roots and roots length in 'SV1' selection (P. fruticosa) at the highest IBA concentration.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The number of roots per explant and root length were highest in the medium supplemented with 2 mg•l -1 IBA (Table 8). Similar results were reported by Dorić et al (2014) who obtained the maximum number of roots and roots length in 'SV1' selection (P. fruticosa) at the highest IBA concentration.…”
Section: Resultssupporting
confidence: 89%
“…DKW medium containing 0.5 mg•l -1 BA was used for Gisela slow growth storage (Lambardi et al 2006). Dorić et al (2014) used this medium to the in vitro propagation of different cherry rootstocks, including 'Gisela 6'. Although MS medium is still most widely used, it is often replaced by media of lower salt concentration, especially those with lower nitrogen content, including the content of ammonium nitrate which is 1650 mg•l -1 in MS medium and 1416 and 400 mg•l -1 in DKW and WPM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Gisela 5 low-vigorous cherry rootstock is mainly propagated by micropropagation throughout the year (Ružić and Cerović, 2002;Ružić and Cerović, 2003). Bošnjaković et al (2013) and Dorić et al (2014) reported successful micropropagation when dormant buds, rather than actively growing shoot tips, were used as an explant source in P. fruticosa Pall. and P. mahaleb L., regardless of genotype diversity.…”
Section: Resultsmentioning
confidence: 99%
“…To break dormancy, Druart (2013) recommended cold storage of twigs for 1 month at 2 °C. In P. fruticosa and P. mahaleb, dormancy did not adversely affect culture initiation, multiplication, shoot elongation, or rooting (Bošnjaković et al, 2013;Dorić et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation